Notes to the species composition of the genus Paramacrobiotus Guidetti et al., 2009 (Tardigrada, Eutardigrada, Macrobiotidae) - Degma, Peter (Zootaxa, 2013)
Summary: For this paper I analyzed the descriptions of all seventy seven currently known Macrobiotus species with three macroplacoids, with or without a microplacoid, to ascertain if they fit to the morphological diagnosis of the genus Paramacrobiotus Guidetti et al., 2009. Most (sixty three species) differed from the genus Paramacrobiotus characters as they were either members of the Macrobiotus harmsworthi and furciger species groups or did not possess the combination of two unique genus characters (elongated macroplacoids and microplacoid considerably distant from the third macroplacoid, if present). Insufficient descriptions for a further ten species means their taxonomic positions remain unclear. Four Macrobiotus species are transferred to the genus Paramacrobiotus and their new taxonomic position is Paramacrobiotus danielisae (Pilato, Binda & Lisi, 2006) comb. nov., Paramacrobiotus hapukuensis (Pilato, Binda & Lisi, 2006) comb. nov., Paramacrobiotus priviterae (Binda, Pilato, Moncada & Napolitano, 2001) comb. nov. and Paramacrobiotus sklodowskae (Michalczyk, Kaczmarek & Węglarska, 2006) comb. nov.